Introduction to Arabic Egyptian Arabic for first-year students - Ghazy, Amira; Eissa, Abdulrahman; Elsherif, Hanan; Hollenberg, David; Loy, Benjamin; Rizk, Kerlos (Open textbook library., 2023)
This book presents materials for mastering the Arabic alphabet and the student's first steps in Egyptian Arabic.